Pelayanan Komprehensif pada Pasien Anak dengan Varicella Melalui Home Visit Menggunakan Family Folder - Adista, Muhammad Ansari; Aini, Zahratul; Syahrizal, Syahrizal; Fuada, Nurul; Moneta, Lily Rezky (Yayasan Literasi Sains Indonesia, 2023)
Home visit is one of the leading health service programs carried out by the health center. Various important information can be obtained from home visit activities, information on the health of family members, relationships between family members and illnesses suffered by each family member. One of the instruments that can be used in home visit activities is the family folder which also functions as a medical record. Community service activities carried out in the form of home visits to one patient with varicella in the working area of ​​the Batoh Health Center, Lueng Bata District, Banda Aceh City. Home visit activities to the preparation of reports are supervised by supervisors from the Family Medicine Section/Department of the Faculty of Medicine, Syiah Kuala University, Banda Aceh. Home visits were carried out twice in one family. The aim is to evaluate treatment and obtain more information about the patient's health condition, next of kin to the patient's and family's living conditions. Home visit activities are complemented by completing the Family Folder instrument which consists of a genogram, family life cycle, family map, family APGAR, family SCREEM and family life line.